Participación de los padres de familia o representantes legales en el apoyo del aprendizaje en el segundo año de educación básica en la Unidad Educativa Once de Noviembre, en la ciudad de Latacunga - Mena Barthelotty, Alicia de las Mercedes (2015)
The present researching is an important topic due to the real life to some parents in relationship with their children, so that parents „participation in the teaching, learning process in so Important because of they are the hearth in the family, they can share their feelings, emotions, experiences, knowledge and human values. The objective in the investigations consisted in determine the effectivity in the parents and legal agents like a help tool in the learning to the children in the second year of basically education for improving the interrelation with them. Another pertinent factor in our proposal is the pedagogical motivation through the parents that means the harmony in the training intellectual and personal development. It was applied the cuali-cuantitativa bibliography, descriptive and the field research, and the techniques to collect data were the surveys and the interviews with the questioner application, so using the statistic method was possible to identify the results in our population. All of the aspects expose before permits us to get a conclusion that it is possible to learn in a best way when there is an excellent relationship among them, in spite of conscious with a guide in workshops, strategies, techniques, methods, living experiences and improve the educative quality in our life.